2019
DOI: 10.19109/ejpp.v6i1.3203
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles and English Proficiency of Undergraduate EFL Students at One State Islamic University in Sumatera, Indonesia

Abstract: This study investigated (1) the correlation between each learning style and English proficiency, and investigated (2) the influence of each learning style to English proficiency of undergraduate EFL students of one state Islamic University in Sumatera, Indonesia. The study was in the form of correlational research method. The population of the study was 537 active EFL students. By using purposive sampling technique, there were 82 students involved as participants. The data were gained by using two instruments:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…It is concluded that there is a combination of learning styles since participants have developed the four styles; nevertheless, the reflectors prevail at a very high level, followed by the activists, pragmatists, and finally, the theorists. However, teachers may promote the development of the four learning styles because that can lead to successful learning outcomes and help students develop qualities language learners need (Beeve, 1998) That could be achieved by raising awareness among students about the importance of developing and combining the four learning styles' characteristics (Marzulina, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is concluded that there is a combination of learning styles since participants have developed the four styles; nevertheless, the reflectors prevail at a very high level, followed by the activists, pragmatists, and finally, the theorists. However, teachers may promote the development of the four learning styles because that can lead to successful learning outcomes and help students develop qualities language learners need (Beeve, 1998) That could be achieved by raising awareness among students about the importance of developing and combining the four learning styles' characteristics (Marzulina, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Their findings showed that reflector, theorist, and divergent styles correlate positively with academic performance. Some researchers suggest considering students' LS in the instruction so that students succeed in their learning process (Bahamón, Vianchá, Alarcón & Bohórquez, 2013;Biabani, & Izadpanah, 2019;Castro & Guzmán, 2005;De Moya, 2011;Hervás, 2008;Marzulina et al, 2019;Payaprom, & Payaprom, 2020;Taheri et al, 2019).…”
Section: Learning Styles Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Students must learn English as one of international languages is the most widely used language in the world (Abrar et al, 2018;Marzulina, Pitaloka, & Yolanda, 2019;Mukminin et al, 2019). In Indonesia, English as foreign language is learned by students of Elementary school, Junior High School, Senior High School and Vocational School , until University level (Marzulina, Mukminin, et al, 2019,).…”
Section: The Interpretation Of Statistical Analysismentioning
confidence: 99%
“…English plays an important role in our everyday life. It is known that English is an international language since it has been largely spoken among foreign language speakers (Marzulina, Pitaloka & Yolanda, 2019). In the 2013 curriculum for senior high school, English subject has some specific purposes.…”
Section: Introductionmentioning
confidence: 99%